2019
DOI: 10.1142/s1363919619500452
|View full text |Cite
|
Sign up to set email alerts
|

Triggering Subordinate Innovation Behavior: The Influence of Leaders’ Dark Personality Traits and Level 5 Leadership Behavior

Abstract: The present study investigates the influence of level 5 leadership, a leadership approach based on humility and professional will, on subordinate’s innovation behavior at work. The main aim is to shed further light on the understanding of how leadership can foster innovative behavior. Further we test if the dark triad of personality, consisting of narcissism, Machiavellianism and psychopathy, affects the likelihood of being a level 5 leader. Applying partial least squares (PLS) structural equation modelling (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 103 publications
1
10
0
1
Order By: Relevance
“…Considering the foregoing, it is suggested that models first consider OR as a variable explained by innovation and then seek to adopt a comprehensive perspective in order to identify the characteristics or attributes that allow an organization to move toward innovation and resilience (Wen-Dong et al, 2018). In this brief context, Strobl et al (2019) stated that innovation should be conceived as a component that improves OR rather than as a fundamental factor. For example, Neise et al (2021) considered that the deployment of information systems constitutes the backbone of resilience, while Zwane et al (2019) stated that the survival of an organization rests on planning, leadership and conducting an organization under an ambidextrous scheme.…”
Section: Bpmj 281mentioning
confidence: 99%
“…Considering the foregoing, it is suggested that models first consider OR as a variable explained by innovation and then seek to adopt a comprehensive perspective in order to identify the characteristics or attributes that allow an organization to move toward innovation and resilience (Wen-Dong et al, 2018). In this brief context, Strobl et al (2019) stated that innovation should be conceived as a component that improves OR rather than as a fundamental factor. For example, Neise et al (2021) considered that the deployment of information systems constitutes the backbone of resilience, while Zwane et al (2019) stated that the survival of an organization rests on planning, leadership and conducting an organization under an ambidextrous scheme.…”
Section: Bpmj 281mentioning
confidence: 99%
“…Additionally, Sarti (2019) studied a two-dimensional justice model for Italy and concluded that procedural and distributive justice are positively related to workplace engagement. Furthermore, Strobl, Niedermair, Matzler, and Mussner (2019) studied the relationship between leaders' personality traits and innovative behaviors and found that leader humility is positively associated with innovative behaviors among executives in Austria.…”
Section: Discussionmentioning
confidence: 99%
“…Participative behavior, the most dominant characteristics of participative behavior are guiding, discussing, and cooperating with subordinates (Li et al, 2018, Strobl et al, 2018, and Yan & Hassan, 2018. Subordinates, who participate in decision-making process, will morally have a sense of responsibility for their own decisions.…”
Section: Discussionmentioning
confidence: 99%